2001
DOI: 10.1128/jb.183.1.63-70.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Putative Pathogenicity Island from Bovine Staphylococcus aureus Encoding Multiple Superantigens

Abstract: Previous studies have demonstrated that a proportion of Staphylococcus aureus isolates from bovine mastitis coproduce toxic shock syndrome toxin (TSST) and staphylococcal enterotoxin C (SEC). In this study, molecular genetic analysis of one such strain, RF122, revealed the presence of a 15,891-bp putative pathogenicity island (SaPIbov) encoding the genes for TSST (tst), the SEC bovine variant (sec-bovine), and a gene ( A closely related strain, RF120, of the same multilocus enzyme electrophoretic type, random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(193 citation statements)
references
References 33 publications
(22 reference statements)
4
186
0
3
Order By: Relevance
“…In this regard, a recently described operon containing enterotoxin genes (14) is present in the RD1 homologue of MRSA strain 252 (http:͞͞www.sanger.ac.uk). In addition, a pathogenicity island (SaPIbov) described in bovine S. aureus strain RF122 is present in the chromosome of RF122, adjacent to RD13 (15). It is clear that multiple deletion, integration, and recombination events have contributed to the variation in the RDs and the genome overall.…”
Section: Importance Of Horizontal Gene Transfer In the Evolution Of Smentioning
confidence: 99%
“…In this regard, a recently described operon containing enterotoxin genes (14) is present in the RD1 homologue of MRSA strain 252 (http:͞͞www.sanger.ac.uk). In addition, a pathogenicity island (SaPIbov) described in bovine S. aureus strain RF122 is present in the chromosome of RF122, adjacent to RD13 (15). It is clear that multiple deletion, integration, and recombination events have contributed to the variation in the RDs and the genome overall.…”
Section: Importance Of Horizontal Gene Transfer In the Evolution Of Smentioning
confidence: 99%
“…The SaPI1 and SaPIbov1 att sites were identified as short direct repeats at the junctions between conserved chromosomal flanking sequences and inserted DNA, by comparison of a strain that contained an SaPI with one that did not (Lindsay et al, 1998;Fitzgerald et al, 2001). The SaPI2 att site core was identified in the SaPI2 sequence.…”
Section: Accessory Genesmentioning
confidence: 99%
“…On the basis of these results, we proposed that the tst element is a mobile pathogenicity island and designated the RN4282 prototype superantigen pathogenicity island 1 (SaPI1) and that in RN3984, SaPI2 (Lindsay et al, 1998). A third member of the SaPI family was identified in a bovine strain and designated SaPIbov (Fitzgerald et al, 2001) (now known as SaPIbov1), and one or more SaPIs have been identified in all but one of the nine sequenced Staphylococcus aureus genomes (Novick & Subedi, 2007). Around the time that SaPIs were first identified, it was shown by Musser et al (1990) that the vast majority of menstrual TSS strains belong to a single clone, of electrophoretic type (ET) 41, and it became clear with the discovery of the agr groups (Ji et al, 1997) that these strains, including RN3984, were all agr group III, whereas RN4282 was agr group I, was not a member of this clone and was not, in retrospect, a typical menstrual TSS strain.…”
Section: Introductionmentioning
confidence: 99%
“…SAg and SAg-like gene-negative isolates ( , 6, 7, 10, 12, 14, 21 and 22 were isolated from milk samples from cows with recent mastitis and were not included in Smyth et al (2005); the numbers in parentheses refer to the cow and the udder quarter from which the milk sample was obtained. Dsea (seb, sec, sed, seg, seh), staphylococcal enterotoxin a (b, c, d, g, h); selj (selk, selq), staphylococcal enterotoxin-like j (k, q); egc, enterotoxin gene cluster comprising the seg, sei, selm, seln, selo genes, with either the selu gene or two pseudogenes yent1 and yent2 located between the sei and seln genes; SaPIbov, S. aureus pathogenicity island bovine possessing the sec-bovine, sell and tst genes (Fitzgerald et al, 2001;Jarraud et al, 2001;Letertre et al, 2003). dMitogenicity assay (ability to induce proliferation of human T-lymphocytes) results for 29 strains (Smyth et al, 2005) are indicated.…”
Section: Discussionmentioning
confidence: 99%